2018
DOI: 10.1002/ejhf.1378
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐organ dysfunction/injury on admission identifies acute heart failure patients at high risk of poor outcome

Abstract: Background Clinical consequences of an interplay between dysfunction/injury of different end‐organs in acute heart failure (AHF) remain unknown. Methods and results In 284 consecutive AHF patients, end‐organ dysfunction/injury was defined as cardiac [troponin I level above the upper reference limit (URL, > 0.056 ng/mL)], kidney (estimated glomerular filtration rate < 60 mL/min/1.73 m2), and liver [at least one of the following: aspartate transaminase (AST)/alanine transaminase (ALT) > 3 times the URL (> 114 IU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
30
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 36 publications
6
30
1
Order By: Relevance
“…27 Analogically to present analyses, the dysfunction of two organs (kidney, liver, or heart) was related to 3.5-fold higher 1 year mortality. We have demonstrated that any elevation of MELD-XI defined as being above the minimal value (which is 9.44 points) had prognostic significance.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…27 Analogically to present analyses, the dysfunction of two organs (kidney, liver, or heart) was related to 3.5-fold higher 1 year mortality. We have demonstrated that any elevation of MELD-XI defined as being above the minimal value (which is 9.44 points) had prognostic significance.…”
Section: Discussionsupporting
confidence: 71%
“…This observation goes with agreement with recently published data, in which AHF patients presenting with higher number of dysfunctional/injured organs on admission had much worse outcome, than had those with lower numbers or no signs of dysfunction. 27 Analogically to present analyses, the dysfunction of two organs (kidney, liver, or heart) was related to 3.5-fold higher 1 year mortality. 27 Coexistence of hepatorenal dysfunction identified patients with more advanced heart failure (as evidenced by lower ejection fraction, lower systolic blood pressure, higher NT-proBNP, higher rate of history of chronic heart failure, and higher rates of oedema), but the association with poor outcomes remained highly statistically significant after multivariable adjustment.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…15, [216][217][218] Multiple factors may contribute to the poor outcomes of the patients after the hospitalization for acute HF, including socioeconomic factors, poor patient support, and poor adherence to prescribed medications. 24, [223][224][225][226][227] Unfortunately, strategies aimed at a better medical treatment of the acute phase, have failed to improve outcomes in major multicentre trials. 222 Other mechanisms are more directly related with congestion and possibly with myocardial, renal, and hepatic injury with persistent organ dysfunction.…”
Section: Acute Heart Failurementioning
confidence: 99%